Determinants of primary market spread in developing securitization in Malaysia : a panel study / Mohammed Hariri Bakri - Bakri, Mohammed Hariri (Institute of Graduate Studies, UiTM, 2015)
Securitization is the process of transforming illiquid assets into rated long-term marketable securities that measures the relationship between securitized assets and market spread. The previous researches provided some evidences on the relationship between the nature of the assets and the primary market spread. Their models provide predictions on how other pricing characteristics affect US and Euro markets. However, emerging markets, notably Malaysia, remain to be testified, and hence these pending results have motivated this study to testify other tests with reference to the Vink Model to fill the literature gap. Further research found that although credit ratings are the most important variables to determine loan spread at issue date, investors appear not to rely exclusively on these ratings, as well as liquidity and leverage beyond the assigned credit rating. The first objective statement to provide empirical contribution variable such as Liquidity and Leverage as determinant of the primary market spread based on Vink regression model of 2008 and 2012. The result shows that liquidity and leverage are significant determinant in the regression model…